2018
DOI: 10.4239/wjd.v9.i10.172
|View full text |Cite
|
Sign up to set email alerts
|

Topical application of platelet-rich plasma for diabetic foot ulcers: A systematic review

Abstract: AIMTo determine if topical application of platelet-rich plasma (PRP) to diabetic foot ulcers (DFUs) results in superior healing rates.METHODSA systematic review was registered with PROSPERO and performed using PRISMA guidelines. Level I-IV investigations of topical PRP application in DFUs were sought in multiple databases including: MEDLINE, Web of Science, and Cochrane Central Register of Controlled Trials. The search terms used were “platelet rich plasma”, “diabetes”, “ulcers”, and “wound”. The Modified Cole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(38 citation statements)
references
References 28 publications
1
31
0
2
Order By: Relevance
“…In the present study, out of the 50 study participants, 70% of the patients were more than 50 years of age. This is expected as usually older age is associated with a longer duration of diabetes which directly increases risk of 15,[17][18][19] The study population in the present study was mostly male. This finding was in line with findings in former studies.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…In the present study, out of the 50 study participants, 70% of the patients were more than 50 years of age. This is expected as usually older age is associated with a longer duration of diabetes which directly increases risk of 15,[17][18][19] The study population in the present study was mostly male. This finding was in line with findings in former studies.…”
Section: Discussionmentioning
confidence: 96%
“…Various studies have clinically proven that administration of PRP dressings achieve a faster healing rate and much shorter healing times, better wound closure, lesser adverse effects such as maceration and contact dermatitis, minimal chances of infections, and lesser reopening of wounds. 10,11,13,15,19,20,24,25…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…6 Local and cyclic administration of platelet-rich plasma (every two weeks) results in statistically faster epithelialisation and closure of the wound, improved sensation and nerve regeneration, and fewer complications compared to standard surgical treatment. 1,24,27,28 Moreover, the combination of standard surgical treatment and platelet-rich plasma therapy will reduce capillary bleeding (elimination of drains), diminish pain and swelling, shorten treatment time. 24 Highly concentrated PRP was also used in treatment of androgen alopecia (AGA), commonly affecting men and women.…”
Section: Osocze Bogatopłytkowe W Medycynie Estetycznejmentioning
confidence: 99%
“…6 Miejscowe i cykliczne podawanie osocza bogatopłytkowego (co ok. 2 tygodnie) powoduje statystycznie szybszą epitelializację i zamknięcie rany, poprawę uszkodzonego czucia i regenerację nerwów oraz mniejsze powikłania w porównaniu z standardowym leczeniem chirurgicznym. 1,24,27,28 Ponadto skojarzenie klasycznego leczenia chirurgicznego i terapii osoczem bogatopłytkowym redukuje krwawienie włośniczkowe (brak konieczności stosowania drenów), zmniejszenie bólu i obrzęku, krótszy czas rekonwalescencji. 24 Wysokoskoncentrowane PRP zastosowano Anitua et al showed positive effects of platelet concentrates on tanocytes, proving their effect on the proliferation of these cells and the release of activators of angiogenesis.…”
Section: Platelet-rich Plasma In Orthopaedicsunclassified